A Bibliometric Analysis of Talent Development and Upskilling Strategies in the Global Palm Oil Sector - Judijanto, Loso; Kurniawan, Kurniawan (Westscience Press, 2025)
This study performs a bibliometric analysis of international research on talent development and upskilling methods within the palm oil industry from 2000 to 2025. Data from the Scopus database were utilized to evaluate 178 articles using Bibliometrix (R-package) and VOSviewer to delineate publication trends, collaboration networks, and theme groupings. Findings indicate that the majority of palm oil research emphasizes sustainability, environmental governance, bioenergy, and climate change, whereas themes related to human capital and workforce development are little investigated. Malaysia and Indonesia excel in this domain, bolstered by institutions including Universiti Putra Malaysia, Universiti Teknologi Malaysia, and Badan Riset dan Inovasi Nasional (BRIN). The results underscore the necessity of incorporating upskilling and talent strategies into sustainability initiatives, connecting environmental management with human resource innovation. This study conceptually contributes by utilizing the Resource-Based View (RBV) and Dynamic Capabilities frameworks to elucidate how workforce competences facilitate sustainable transformation. The report emphasizes that the future competitiveness and sustainability of the palm oil business rely on technological and ecological advances as well as strategic human-capital development along the value chain.